KEPEMIMPINAN INSTRUKSIONAL DAN BUDAYA MUTUSEKOLAH: KAJIAN LITERATUR TERHADAP PENINGKATAN KUALITAS PEMBELAJARAN - Rismayani, Risha; Rizki, Ridonal; Gistituati, Nurhizrah; Rismayani, Rusdinal; Rismayani, Nellitawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of instructional leadership and school qualityculture in improving the quality of learning through a Systematic Literature Review(SLR) approach. The method used is a qualitative approach with literature studytechniques involving various relevant international journals, books, and scholarlysources within a specific time frame. Data were collected through processes ofidentification, selection, and analysis of articles based on inclusion and exclusioncriteria, and then synthesized thematically to obtain a comprehensiveunderstanding of the relationships among variables. The results indicate thatinstructional leadership has a significant influence on improving teacherperformance, learning effectiveness, and student learning outcomes. On the otherhand, school quality culture has been proven to strengthen commitment to qualitystandards, enhance collaboration among teachers, and encourage instructionalinnovation. The integration of instructional leadership and quality culturedemonstrates a synergistic relationship in creating an effective, adaptive, andsustainable learning system. This study concludes that instructional leadershipand school quality culture are two key factors that complement each other inimproving the quality of learning. Therefore, strengthening both aspectssimultaneously becomes an important strategy in efforts to enhance the quality ofeducation in schools.Keywords: instructional leaders